Investigations on heavy-duty gearboxes temperature and the viscosity of the lubricant through simulation and experiment method / Navin Kumar Ganesan - Navin Kumar, Ganesan (2022)
The development of gear transmissions nowadays is focusing on four main reasons which are noise, vibration, and harshness to reduce the surrounding sound pollution, load capacity, wear and tear which will lessen friction and productivity. Gearboxes are as often as possible outlined conservatively with a supply of oil to ensure operational unwavering quality. The present study will focus on the viscosity of plastic extruder line gearbox oil and how the oil temperature is maintained. In this study, two types of lubricants will be used to demonstrate which lubricant performs well. use a calculation method to prove the efficiency of the heat exchanger before and after the gear oil temperature. An earlier investigation focused more on oil temperature and did not show what would happen due to high oil temperature and didn’t demonstrate simulation results with gear oils of actual viscosity. This study aims to collect actual data and prove it by simulation and experimental methods. This research is more effective for high voltage cable industry production because normally the extrusion line will be run for two or three weeks nonstop to reach the target of the order. The data also show an exponential trend between the average wear rates and the surface fatigue lives. Lubricants with similar viscosities but differing additives and compositions had somewhat differing gear surface fatigue lives and wear rates. It determined the way to reduce gearbox portion temperature and maintain the lubricant additive and also the viscosity index number. The method to eliminate water and acid contained in the plastic extruder gearbox during the machine operating at high temperature.